Advanced Communications Technology Satellite (ACTS) fade compensation protocol impact on very small-aperture terminal bit error rate performance. - Cox, C.B.
The Advanced Communications Technology Satellite (ACTS) communications system operates at Ka band. ACTS uses an adaptive rain fade compensation protocol to reduce the impact of signal attenuation resulting from propagation effects. The purpose of this paper is to present the results of an analysis characterizing the improvement in VSAT performance provided by this protocol. The metric for performance is VSAT bit error rate (BER) availability. The acceptable availability defined by communication system design specifications is 99.5% for a BER of 5E-7 or better. VSAT BER availabilities with and without rain fade compensation are presented. A comparison shows the improvement in BER availability realized with rain fade compensation. Results are presented for an eight-month period and for 24 months spread over a three-year period. The two time periods represent two different configurations of the fade compensation protocol
Keywords: 19.44 GHz; 24 month; 29.236 GHz; 29.291 GHz; 3 year; 8 month; ACTS; Advanced Communications Technology Satellite; BER availability; Ka band; SHF; VSAT performance; Adaptive rain fade compensation protocol; Bit error rate performance; Communication system design specifications; Propagation effects; Signal attenuation; Very small-aperture terminal